(untitled) (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was conducted at the Regional Agricultural Research Station, Ishurdi, Pabna during the growing season of 2013-14 with eighteen hybrid lines of pointed gourd and BARI Hybrid Patal -1 as check to observe their performances for yield, yield attributes and other morphological characters. The experiment was laid out in randomized complete block design with three replications. The maximum vine length (242.00 cm) and nodes/plant (18.30) was recorded from PG018xM2. Shoots/plant ranged from 12.50 (PG027xM2) to 4.66 (PG008 M1). The maximum number of fruits/plant (160.00) was obtained from PG009xM2 followed by PG012xM1 (154.66). Individual fruit weight was recorded highest (50.10 g) in PG027xM2, which was very close to PG008xM2 (48.00) and PG018xM2 (47.00 g). Weight of fruits/plant ranged from PG009xM2 (6.86 kg) to PG022xM1 (3.01 kg). The highest pulp weight was recorded in PG027xM2 (44.20 g) which was statistically similar to PG008xM2 (42.20 g). Three different leaf colour (light green, green and deep green), two types of leaf tip (pointed and blunt) and four types of leaf margin (slightly serrated, serrated, entire and undulated) were found among the hybrid lines. Four fruit colour (whitish, light green, green and dark green), four fruit stripes (no stripe, white, green white and light green) and three types of fruit curvature (slightly curved, curved and straight) were observed in different lines. The line PG009xM2 showed better performance in respect of fruits/plant and weight of fruits/plant and thus gave the highest yield (45.74 t/ha). The lines PG008xM2, PG007xM2, PG017xM2, PG027xM2 and PG014xM1 also produced better yield (39.23 - 35.58 t/ha). Therefore, the lines PG014xM1, PG007xM2, PG008xM2, PG009xM2 and PG017xM2 should be subjected for further evaluation to release as variety. Bangladesh J. Agril. Res. 43(3): 383-393, September 2018